A comprehensive overview of mitochondrial DNA 4977-bp deletion in cancer studies - Abdul Aziz Mohamed Yusoff; Wan Salihah Wan Abdullah; Siti Zulaikha Nashwa Mohd Khair; Siti Muslihah Abd Radzak (Frontiers Media S.A., 2019)
Mitochondria are cellular machines essential for energy production. The biogenesis of mitochondria is a highly complex and it depends on the coordination of the nuclear and mitochondrial genome. Mitochondrial DNA (mtDNA) mutations and deletions are suspected to be associated with carcinogenesis. The most described mtDNA deletion in various human cancers is called the 4977-bp common deletion (mDNA4977) and it has been explored since two decades. In spite of that, its implication in carcinogenesis still unknown and its predictive and prognostic impact remains controversial. This review article provides an overview of some of the cellular and molecular mechanisms underlying mDNA4977 formation and a detailed summary about mDNA4977 reported in various types of cancers. The current knowledges of mDNA4977 as a prognostic and predictive marker are also discussed.